The Digital Communication of Male Birth Control in Surabaya - Hilda Wono; Hadjar Chanissa Nur Malika; Ergita Jeny Ardaneshwari; Jessica Nathalia Hermawan (School of Communication Science and Media Business, 2023)
The spread of information is now becoming faster along with the development of digital technology. One of them is the development of digital communication that is accelerating, especially with the Covid-19 pandemic. The existence of the pandemic has made the need for digital communication technology needed in various fields, one of which is the field of marketing. Not only the private sector, but marketing is also carried out by the government in Surabaya. Dinas Pengendalian Penduduk, Pemberdayaan Perempuan dan Perlindungan Anak (DP3APPKB) Surabaya uses digital communication in the form of applications and the web to market family planning for men, which is decreasing its acceptor drastically. To introduce more broadly and increase the acceptor of male birth control, DP3APPKB Surabaya uses digital communication to reduce face-to-face meetings. This study looked at the form of digital communication carried out by DP3APPKB Surabaya using qualitative description research methodology. Data collection for this study used FGD (focused group discussion) with 5 seniors from PKB Surabaya and documentation studies. The findings of this study highlight the rapid development of digital communication within government channels, with a proliferation of applications and websites. However, it also underscores a significant deficiency in the availability of comprehensive information related to male birth control on these digital platforms. Keywords: digital communication, marketing, man family planning, applications, website